2021
DOI: 10.21009/biosferjpb.18663
|View full text |Cite
|
Sign up to set email alerts
|

Students' interest and cognitive learning outcomes: Biology education in high schools during COVID-19

Abstract: The aim of this study to determine the interest in studying biology and the effect of interest in studying biology on the learning outcomes of cognitive biology during the Covid-19 pandemic. Based on several previous studies, it is known that online learning during the Covid-19 pandemic greatly influenced students' interest in learning biology. However, it is not yet known the level of interest in learning itself due to the effect of online learning, and it is not yet known the magnitude of the influence of in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…The benefits of student interest on academic achievement and learning have been well-documented (Hidi & Renninger, 2006 ; Schiefele et al, 1992 ). In a recent study, Gustia and Suhartini ( 2021 ) found that higher levels of interest in learning about biology during COVID-19 significantly increased students’ cognitive outcomes for biology. Yet, the specific topics of interest to students related to COVID-19 have not been explicitly explored.…”
Section: Introductionmentioning
confidence: 99%
“…The benefits of student interest on academic achievement and learning have been well-documented (Hidi & Renninger, 2006 ; Schiefele et al, 1992 ). In a recent study, Gustia and Suhartini ( 2021 ) found that higher levels of interest in learning about biology during COVID-19 significantly increased students’ cognitive outcomes for biology. Yet, the specific topics of interest to students related to COVID-19 have not been explicitly explored.…”
Section: Introductionmentioning
confidence: 99%
“…Other internal factors related to success learning process are physiological factors which include student health and psychological factors, such as intelligence, learning interest, perception, attitude, talent, self-confidence, learn readiness and student effort in following the learning process to achieve the expected results (Daryanti, 2016;Gustia & Suhartini, 2021;Husamah & Pantiwati, 2014;Yuranda & Nurhayati, 2016).…”
Section: Figure 2 Frequency Distribution Of Students ' Perception Sco...mentioning
confidence: 99%
“…Cognitive learning outcomes refer to the measurable level of students' actual abilities in terms of concept acquisition, which is a direct consequence of their individual efforts in the learning process (Bahri, Corebima, Amin, and Zubaidah, 2016). The role of metacognitive awareness in enhancing students' cognitive learning outcomes is significant, as it exhibits a positive correlation with such outcomes (Millis, 2016;Gustia & Suhartini, 2021). According to the study conducted by Hermawan, Abidin, and Junedi (2018), there exists a notable association between metacognitive awareness and cognitive learning outcomes.…”
Section: Introductionmentioning
confidence: 99%